Analysis Of The Impact Of Social Media, Fear Of Missing Out (FOMO), And Income On The Consumer Behavior Of Millennials In Medan City (Program Studi Ekonomi Syariah, Fakultas Agama Islam Universitas Islam Riau, 2025)
This study investigates the influence of social media and income on consumer behavior among millennials in Medan City, with Fear of Missing Out (FOMO) serving as a mediating variable. The research is motivated by the growing trend of digital consumerism and the psychological pressure faced by the younger generation in maintaining social relevance. Utilizing a quantitative approach, the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4. 0 to analyze data collected from 100 respondents—millennials who are active social media users and have engaged in online shopping within the last three months. The findings reveal that social media significantly affects both FOMO and consumer behavior. Income does not directly influence consumer behavior, but significantly impacts FOMO. Furthermore, FOMO fully mediates the relationship between income and consumer behavior, and partially mediates the relationship between social media and consumer behavior. These results highlight FOMO as a key psychological mechanism driving consumption in the digital era, often overriding traditional economic rationality. This study contributes to the growing literature on digital consumer psychology by integrating economic and psychological variables within a unified model. Practically, the findings offer insights for policymakers, educators, and marketers to design effective interventions that promote financial literacy and responsible digital consumption among youth.